Foraminifera and bacterial activity in oil spillimpacted mangrove, Guanabara Bay, Brazil - Fontana, Luiz F.; Laut, Lázaro L. M.; Figueiredo Jr., A.G.; Crapez, M. A. C.; Rosa, T. D. L. (Anuário do Instituto de Geociências, 2006)
Abstract